Role of bacterial infection in the epigenetic regulation of Wnt antagonist WIF1 by PRC2 protein EZH2 - Roy, Badal C. (Oncogene, 2014)
The Enhancer of Zeste Homolog-2 (EZH2) represses gene transcription through histone H3 lysine-27-trimethylation (H3K27me3). Citrobacter rodentium (CR) promotes crypt hyperplasia and tumorigenesis by aberrantly regulating Wnt/β-catenin signaling. We aimed at investigating EZH2’s role in epigenetically regulating Wnt/β-catenin signaling following bacterial infection. NIH:Swiss outbred and Apc(Min/+) mice were infected with CR (10(8)cfu); BLT1(−/−)Apc(Min/+) mice, AOM/DSS-treated mice and de-identified human adenocarcinoma samples were models of colon cancer. Following infection with wild type but not mutant CR, elevated EZH2 levels in the crypt at days-6 and 12 (peak hyperplasia) coincided with increases in H3K27me3 and β-catenin levels, respectively. Chromatin immunoprecipitation revealed EZH2 and H3K27me3’s occupancy on WIF1 (Wnt Inhibitory Factor-1) promoter resulting in reduced WIF1 mRNA and protein expression. Following EZH2 knockdown via siRNA or EZH2-inhibitor DZNep either alone or in combination with HDAC inhibitor SAHA, WIF1 promoter activity increased significantly while overexpression of EZH2 attenuated WIF1-reporter activity. Ectopic overexpression of SET domain mutant (F681Y) almost completely rescued WIF1 reporter activity and partially rescued WIF1 protein levels while H3K27me3 levels were significantly attenuated suggesting that an intact methyltransferases activity is required for EZH2-dependent effects. Interestingly, while β-catenin levels were lower in EZH2-knocked-down cells, F681Y mutants exhibited only partial reduction in β-catenin levels. Besides EZH2, increases in miR-203 expression in the crypts at days-6 and 12 post-infection correlated with reduced levels of its target WIF1; overexpression of miR-203 in primary colonocytes decreased WIF1 mRNA and protein levels. Elevated levels of EZH2 and β-catenin with concomitant decrease in WIF1 expression in the polyps of CR-infected Apc(Min/+) mice paralleled changes recorded in BLT1(−/−)Apc(Min/+), AOM/DSS and human adenocarcinomas. Thus, EZH2-induced downregulation of WIF1 expression may partially regulate Wnt/β-catenin-dependent crypt hyperplasia in response to CR infection.